Long-term results of simplified frozen elephant trunk technique in complicated acute type A aortic dissection: A case–control study. (October 2016) - Kobayashi, Misato; Chaykovska, Lyubov; van der Loo, Bernd; Nguyen, Thi Dan Linh; Puippe, Gilbert; Salzberg, Sacha; Ueda, Hideki; Maisano, Francesco; Pecoraro, Felice; Lachat, Mario
Aim: To describe the long-term experience of a simplified frozen elephant trunk technique (sFETT) used in complicated acute type A aortic dissection (AAAD) treatment. Methods and results: Between January 2001 and December 2012, 34 patients (mean age 59.9 ± 11.0 years) with complicated AAAD (DeBakey I) underwent an emergency surgery including sFETT. sFETT consisted in gluing the dissected aortic arch wall layers with gelatine-resorcinol adhesive and video-assisted antegrade open arch aortic stent-graft deployment in the arch or proximal descending aorta. In addition to sFETT, the aortic root was addressed with standard techniques. A 30-day mortality was 14.7% (five patients) due to bleeding (1), multiple organ failure (2), and colon ischemia (2). Postoperative morbidity included neurological (2), renal (1) and cardio-pulmonary complications (4), as well as wound infection (1). Mean follow-up was 74.4 ± 45.0 months. Actual survival rates were 73.5% at 1 year, 70.2% at 5 years, and 58.5% at 13 years of follow-up. Six patients died during long-term follow-up from heart failure (1) and unknown reasons (5). Five patients required reoperation for aortic arch (3) or aorto-iliac (2) progression of aneurysm during the mid- and long-term follow-up. The remaining patients showed favorable evolution of the dissected aorta with false lumen occlusion in most cases and stable aortic diameters. Conclusions: In AAAD patients, sFETT as used in our series is an easy and safe technique to repair the aortic arch. Long-term results after sFETT showed false lumen occlusion and stable aortic diameter in up to 13 years of follow-up.